The Role of Analysts? Forecasts in Accounting-Based Valuation: A Critical Evaluation - Cheng, Qiang (Review of Accounting Studies, 2005)
This paper critically evaluates the use of analysts’ forecasts in accounting-based valuation. Specifically, I assess the usefulness and the limitation of analysts’ forecasts in predicting future earnings and in explaining the market-to-book ratio, in light of a comprehensive set of 22 explicit information items, including: economic rent proxies, conservative accounting proxies, earnings quality signals, transitory earnings proxies, industry characteristics, and risk and growth proxies. While analysts’ forecasts capture 45–83% of the information from these sources depending on model specifications, they do not appear to fully incorporate certain information items. In particular, proxies for conservative accounting and transitory earnings are incrementally useful in predicting future earnings; proxies for economic rents, conservative accounting, and risk are incrementally useful in explaining the market-to-book ratio. Collectively, these results validate the use of analysts’ forecasts as a parsimonious proxy for forward-looking information in accounting-based valuation and suggest how to improve on their use.